PEMANFAATAN MULTIMEDIA INTERAKTIF DALAM MENINGKATKAN HASIL BELAJAR SISWA KELAS V SEKOLAH DASAR - Dewi, Anggra Lita Sandra (Lembaga Penelitian dan Pendidikan Mandala, 2022)
The low student learning outcomes on the type of work for class V SDN Siwalanpanji Sidoarjo can be seen from the results of obtaining student test scores as much as 40% are declared to have passed the KKM while 60% percent are declared not to have passed the KKM. This is due to the application of learning strategies and learning media that are not in accordance with the needs of students so that the process of learning activities does not have a direct impact on students. So that the development of interactive multimedia-based teaching materials needs to be developed in the process of learning activities. The purpose of this study was to determine the improvement of student learning outcomes in the use of interactive multimedia in fifth grade elementary school students. This study used 2 cycles with 30 students. In the first cycle, the completeness of learning outcomes reached 50% (15 students passed) and in Cycle II the completeness of student learning outcomes reached 90% (27 students passed). From this study it can be concluded that the use of interactive multimedia can improve the learning outcomes of fifth grade elementary school students.